Importance of monitoring the use of direct oral anticoagulants in older patients in community pharmacies in Serbia - Andjelković, Jasna; Kovačević, Milena; Miljković, Branislava (Archives of Pharmacy, 2022)
The use of direct oral anticoagulants (DOACs) in older patients carries a higher risk of thromboembolic events and anticoagulant-associated bleeding, in comparison to younger patients. The aim of this study was to identify drug-related problems and pharmacists’ interventions related to DOACs. A prospective survey was conducted at Pharmacy Kragujevac from 2019 to 2022. Data were obtained for patients aged ≥65 with DOACs prescription, using a questionnaire that was filled out during a conversation with the patient. The study included 78 patients, aged 71±8 years, 68% of whom were men. On average, patients had 3±1 diagnoses and 5±2 medications. Apixaban was used by 44%, rivaroxaban 31%, dabigatran 25%. Atrial fibrillation was present in 59% and deep vein thrombosis in 41%. A total of 102 DRPs were detected: inappropriate drug use in 24% (e.g. taking rivaroxabane without food, opening dabigatran capsules), adherence in 38%, low dose in 12%, high dose in 9%, while potential interactions were present in 41%. Among the significant risk factors, 23% had unstable blood pressure, 33% were not informed about the importance of renal function monitoring during drug use, and one patient had low hemoglobin level. Two patients were referred to a doctor, one of whom had an episode of bleeding. Pharmacists educated all the patients about the importance of adherence, proper application of DOACs and the importance of DOACs alert card. The results demonstrate the necessity of monitoring the use of DOACs in elderly patients by implementing standardized pharmaceutical services at the primary level of health care.